Acute psychiatric care for pediatric patients. (2nd April 2020) - Reynolds, Elizabeth K.; Gorelik, Sasha; Kook, Minjee; Kellermeyer, Kyle
Abstract: Higher level or acute psychiatric care for youth is intended to be active but short-term treatment focussing on crisis stabilisation, assessment, safety monitoring, and longer-term treatment planning. The focus of this article is on describing common challenges and the effort to address these challenges through new approaches to acute psychiatric care for children and adolescents. The review finds that (1) inpatient paediatric psychiatry beds are in high demand and often difficult to access, (2) there are a number of common challenges these units face including managing length of stays, readmissions, and adverse events, and (3) there are encouraging therapeutic approaches adapted for this setting. There is still much work to be done to advance the evidence-base for acute psychiatric care for youth particularly in defining and assessing an effective admission. Paediatric psychiatry patients are a vulnerable population and call for our best tools to be put to use to improve the quality and safety of care.